Interpersonal Skills Among Fourth- and Fifth-Year Medical Students: Validation of an Assessment Tool. Issue 2 (April 2018) - Morel, Alexandre; Hardouin, Jean-Benoit; Pottier, Pierre
Abstract : Objective: The aim of this study was to validate a French version of the standardized patient satisfaction questionnaire (SPSQ), an interpersonal skills assessment form, originally published in English, destined to be completed by SPs and used as a validated tool for the evaluation of communication skills of French medical students, during ambulatory care consultations. Methods: During the academic year, fourth- and fifth-year medical students participated in mock ambulatory care consultations. The French SPSQ was completed by 16 SPs who performed scenarios written by professors of medicine. Validity evidence for test content, response process, internal structure, and relation to other variables was determined by calculating the Cronbach α coefficient, the Loevinger H index (response coherence), intraclass coefficients, the differences between fourth- and fifth-year students and by using item correlations as well as the correlation with an independent validated assessment form. G theory was used to identify the sources of variations in the mean of SPSQ. Results: Four hundred thirty-three students were evaluated for a period of 2 months and participated in a total of 1703 mock consultations. The Cronbach α coefficient (0.94) was superior to that of the English SPSQ. The Loevinger H index was good ranging from 0.65 to 0.70. The reproducibility among external observers (intraclass correlation coefficient = 0.67) and between external observers and the SPs (intraclass correlation coefficient = 0.79 and 0.78, respectively) was satisfactory. Results of the French SPSQ were positively and significantly correlated to the scores obtained via an independent, validated, questionnaire ( R = 0.72) and showed a significant difference between fourth- and fifth-year students' scores ( P < 0.0001). G coefficients were estimated at 0.64 and 0.52 for year 4 and year 5, respectively. Conclusions: Validity evidence supports the use of French-version SPSQ scores to screen for students experiencing difficulty with communication.